Childhood Sexual Abuse and Sociodemographic Factors Prospectively Associated with Intimate Partner Violence Perpetration Among South African Heterosexual Men. Issue 2 (14th November 2016) - Teitelman, Anne M.; Bellamy, Scarlett L.; Jemmott, John B.; Icard, Larry; O'Leary, Ann; Ali, Samira; Ngwane, Zolani; Makiwane, Monde
Abstract: Background: Intimate partner violence directed at women by men continues to be a global concern. However, little is known about the factors associated with perpetrating intimate partner violence among heterosexual men. Purpose: History of childhood sexual abuse and other sociodemographic variables were examined as potential factors associated with severe intimate partner violence perpetration toward women in a sample of heterosexual men in South Africa. Methods: Longitudinal logistic generalized estimating equations examined associations of childhood sexual abuse and sociodemographic variables at baseline with intimate partner violence perpetration at subsequent time points. Results: Among participants with a steady female partner, 21.81 % (190/ 871) reported perpetrating intimate partner violence in the past year at baseline. Having a history of childhood sexual abuse ( p < .001), binge drinking ( p = .002), being employed ( p = .050), and more difficulty controlling sexual impulses in order to use a condom ( p = .006) at baseline were associated with self-reported intimate partner violence perpetration in the past year at subsequent time points. Conclusions: With high levels of recent severe physical and/or sexual intimate partner violence perpetration in South Africa, comprehensive interventions are urgently needed. To more fully address gender-based violence, it is important to address associated factors, including exposure to childhood sexual abuse that could impact behavior later in life and that have long-lasting and deleterious effects on men and their female partners.